Virulence gene profile and antimicrobial resistance patterns of Aeromonas hydrophila in farmed catfishes (Heteropneustes fossilis and Pangasianodon hypophthalmus) for the first time in Bangladesh - Farjana Ferdousi; Bushra Benta Rahman Prapti; Alamgir Hasan; Aminur Rahman; Ravi Yadav; Md. Shafiqul Islam; Md. Taohidul Islam; Md. Alimul Islam; Mahbubul Pratik Siddique (PLoS ONE, 2025)
Among several Aeromonas spp., causing diseases in fishes, Aeromonas hydrophila is the most predominant and pathogenic one. This study represents the first molecular detection, virulence profiling, and antibiogram analysis of Aeromonas hydrophila isolated from stinging catfishes (shing; Heteropneustes fossilis) and shark catfishes (pangasius; Pangasianodon hypophthalmus) in Bangladesh. Whole fish samples (n = 140) were collected from fish farming areas of Trishal upazila (stinging catfish 50; shark catfish 20) and Muktagachha upazila (stinging catfish 50; shark catfish 20), under Mymensingh district. Isolation and identification were accomplished through cultural, morphological, biochemical and finally, polymerase chain reaction (PCR) using genus- and species-specific primers, targeting 16S rDNA gene. Out of 140 samples, 38 (27.14%) isolates were found positive for A. hydrophila via conventional and PCR. The PCR-based virulence profiling showed that aerA (44.73%), hlyA (39.74%), asa1 (39.47%), ahyB (60.52%), act (21.5%), ast (28.94), alt (47.36%), ser (44.73%), lip (50%), gcat (23.68%), and ascV (21.05%) genes were detected, however, no aexT was detected. Antibiotic susceptibility test (using disc diffusion method) revealed that highest resistance (other than Penicillin Group) against Aztreonam and Cefuroxime (73.68%), and lowest against Gentamicin and Azithromycin (5.26%). MDR was detected in 71.05% isolates, and 92.11% isolates had MAR index ≥ 0.2. Statistically significant associations were observed between phenotypic resistance and specific virulence genes p ≤ 0.05. It could be concluded that MDR and virulent potential A. hydrophila are prevalent in stinging and shark catfishes of Mymensingh region, which might be a serious threat to sustainable aquaculture, food safety and public health.